The Implementation of “Kampung Inggris” Program on Enhancing Students’ Listening Skill at SMP Muhammadiyah Plus Salatiga - Sari, Siska Karista; Suhailah, Jihana; Cahyono, Guntur (Universitas Pahlawan Tuanku Tambusai, 2026)
This study aims to analyze the effectiveness of the ‘Kampung Inggris’ extracurricular program in helping students at SMP Muhammadiyah Plus Salatiga improve their listening skills. The method used in this study is qualitative descriptive. Data was collected that students at SMP Muhammadiyah Plus Salatiga find English listening skills challenging because several factor such as cognitive skills, time management, etc. The results of this study show that the implementation of the ‘Kampung Inggris’ program involves curriculum changes, real listening activities, and the formation of a culture of speaking English that is mandatory in schools. The teachers interviewed reported that this program has succeeded in improving students' listening skills. This improvement was most evident in students' ability to recognize different accents, understand context, and respond to verbal instructions in real-life situations. The implementation of the ‘Kampung Inggris’ program proved to be an effective and successful measure.